An Investigation into the Barriers Facing Black and Minority Ethnics Within the UK Construction Industry - Ahmed, Vian; Pathmeswaran, Raju; Baldry, David; Worrall , Lisa; Abouen, Sabri (Penerbit Universiti Sains Malaysia, 2008)
The UK construction industry is one of the largest employers, positioned as the country's top employer with over two million employees and projected to continue growth as far as 2011. However, it is facing ongoing skills shortages in a number of professional areas and tends to lack an ethnic diversity of workers compared to the White community of workers across the whole economy. The government’s Ethnic Minority Employment Task Force shows that for any given level of qualification, a Black or ethnic minority person is less likely to be employed, than a similarly qualified White person. Current research into issues surrounding ethnicity, from academia to employment is scarce, particularly in entry and process development within the construction industry. The aim of this paper is to outline the findings from perceptional and experiential barriers of Black and Minority Ethnics (BMEs) students and employees, in order to identify perceptional and actual barriers that lead to the under-representation of BMEs within the construction industry; and also to suggest how better knowledge flow mechanisms could lead to a more balanced development, particularly in terms of ethnic diversification in the UK construction industry. The aim was achieved by adopting qualitative and quantitative methods including questionnaire surveys of undergraduate students in a construction related programme, employees working within the construction industry and interviews with company directors and human resource managers. The image of the construction industry is found to be one of the major barriers for entry into the industry. Language and cultures form additional barriers for a range of ethnic groupings. Support, in the form of recruitment events, training, mentoring, professional networking, as well as work placement and experience schemes, can smooth entry, retention and progression within the construction industry